Survey on intelligent game of computer poker - Weilin YUAN; Zhiyong LIAO; Wei GAO; Tingting WEI; Junren LUO; Wanpeng ZAHNG; Jing CHEN (网络与信息安全学报)
Computer game is the drosophila in the field of artificial intelligence, which has attracted the attention of researchers in artificial intelligence, and has become an advantageous testbed for the research of cognitive intelligence.Poker game can be modeled as dynamic games with imperfect information, definite boundaries and fixed rules.Computer poker AI needs such abilities as dynamic decision-making with incomplete information, identification of misleading and fraudulent behaviors by opponents, and multi-round chips and risk management.Firstly , the development of computer poker game was introduced, which represented by Texas Hold’em poker.Then, typical intelligence game model algorithm, key techniques and existing main problems of computer poker were reviewed analysis.Finally, the future development trends and application prospect of computer intelligent poker game were discussed for cognitive intelligence.